Investment vs. refurbishment: Examining capacity payment mechanisms using mixed complementarity problems with endogenous probability - Muireann Á. Lynch; Mel T. Devine (The Economic and Social Research Institute (ESRI), 2015)
Capacity remuneration mechanisms exist in many electricity markets. Capacity mechanism designs do not explicitly consider the effects of refurbishment of existing generation units in order to increase their reliability. This paper presents a mixed complementarity problem with endogenous probabilities to examine the impact of refurbishment on electricity prices and generation investment. Capacity payments are found to increase reliability when refurbishment is not possible, while capacity payments and reliability options yield similar results when refurbishment is possible. Final costs to consumers are similar under the two mechanisms with the exception of the initial case of overcapacity.
Keywords: Q4; D43; D47; L13; C61; 330; Capacity markets; Reliability; Mixed Complementarity Problem; Stochastic Modelling